Impact of Operational Plans on Forest Cover Area: A Comparative Study of Community Forests in Nepal - Feiersinger, Sebastian J.P.D.; Stilma, Anko A.; Chapagain, Arjun (Journal of Forest and Livelihood, 2025)
Within the middle hills of Nepal, operational plans (OPs) were found to prescribe the same operations, irrespective of species composition, forest conditions, and forest management objectives. It is not clear how, and to what extent, the OPs play a role in practical forest management, or whether they are followed by the members of the community forest user groups (CFUGs) and how this affects the forest cover area. This study assesses whether differences in forest cover area between two community forests can be explained by differences in their OPs and their implementation by the respective CFUGs. To achieve this, three methods were applied: forest cover area measurements using annual landcover data, a directed content analysis of the OPs, and ground truthing through interviews and Likert scale questionnaires. Results revealed a significant difference in the forest cover area: Machhedanda CFUG showed more fluctuation compared to Baluwa Bhanjyang CFUG. The CFUGs differ in OP focus, with Machhedanda more focused on socio-economic development and Baluwa Bhanjyang prioritising forest conservation. Both CFUGs faced communication challenges and struggled to fully implement their OPs. These findings suggest that forest cover area outcomes are not solely influenced by written plans, but also by how CFUGs engage with and implement them.